Alternative scaffolds in radionuclide diagnosis of malignancies - O. D. Bragina; V. I. Chernov; R. V. Zeltchan; I. G. Sinilkin; A. A. Medvedeva; M. S. Larkina (Бюллетень сибирской медицины, 2019)
This review discusses a relatively new class of targeted molecules that is being actively studied for radionuclide diagnosis and treatment of malignancies. The full-size antibodies used so far have non-optimal pharmacological properties, slow distribution in the body, poor penetration into the tissue and kidney excretion, and high immunogenicity, which significantly complicates their use in clinical practice. Over the past decade, a new class of targeted molecules, called “non-immunoglobulin scaffolds” have become popular; they have all the requirements for optimal delivery of a radionuclide to tumor cells. Scaffolds usually are smaller in size in comparison with antibodies, but they are larger than peptides, and are characterized by high affinity and optimal biochemical, biophysical, biological, and economic features. The advantages of such proteins are their stable structure, good penetration into tissues, the possibility of additional functionalization and expression in the bacterial system, which ensures low production costs.The results of preclinical and clinical studies for diagnosis of malignancies using such proteins as affibody, adnectin, DARPins, etc., have demonstrated their high specificity, affinity, good tolerance and low immunogenicity.